Electrochemical Activity of a La0.9Ca0.1Co1−xFexO3 Catalyst for a Zinc Air Battery Electrode. (29th March 2015) - Eom, Seungwook; Ahn, Seyoung; Jeong, Sanghwan
Abstract : The optimum composition of cathode catalyst has been studied for rechargeable zinc air battery application. La0.9 Ca0.1 Co1− x Fe x O3   ( x = 0 – 0.4 ) perovskite powders were prepared using the citrate method. The substitution ratio of Co 2+ with Fe 3+ cations was controlled in the range of 0–0.4. The optimum substitution ratio of Fe 3+ cations was determined by electrochemical measurement of the air cathode composed of the catalyst, polytetrafluoroethylene (PTFE) binder, and Vulcan XC-72 carbon. The substitution by Fe enhanced the electrochemical performances of the catalysts. Considering oxygen reduction/evolution reactions and cyclability, we achieved optimum substitution level ofx = 0.1 in La0.9 Ca0.1 Co1− x Fe x O3 .